Population genetics of PDE4B (phosphodiesterase‐4B) in neglected Native Americans: Implications for cancer pharmacogenetics - Rennan Garcias Moreira; Julia Maria Saraiva‐Duarte; Alexandre Costa Pereira; Martha Sosa‐Macias; Carlos Galaviz‐Hernandez; Meddly Lesley Santolalla; Wagner C. S. Magalhães; Camila Zolini; Thiago Peixoto Leal; Zsolt Balázs; Adrián Llerena; Robert H. Gilman; et al. (Wiley, 2022)
Abstract PDE4B (phosphodiesterase‐4B) has an important role in cancer and in pharmacology of some disorders, such as inflammatory diseases. Remarkably in Native Americans, PDE4B variants are associated with acute lymphoblastic leukemia (ALL) relapse, as this gene modulates sensitivity of glucocorticoids used in ALL chemotherapy. PDE4B allele rs6683977.G, associated with genomic regions of Native American origin in US‐Hispanics (admixed among Native Americans, Europeans, and Africans), increases ALL relapse risk, contributing to an association between Native American ancestry and ALL relapse that disappeared with an extra‐phase of chemotherapy. This result insinuates that indigenous populations along the Americas may have high frequencies of rs6683977.G, but this has never been corroborated. We studied ancestry and PDE4B diversity in 951 healthy individuals from nine Latin American populations. In non‐admixed Native American populations rs6683977.G has frequencies greater than 90%, is in linkage disequilibrium with other ALL relapse associated and regulatory variants in PDE4B‐intron‐7, conforming haplotypes showing their highest worldwide frequencies in Native Americans (>0.82). Our findings inform the discussion on the pertinence of an extra‐phase of chemotherapy in Native American populations, and exemplifies how knowledge generated in US‐Hispanics is relevant for their even more neglected and vulnerable Native American ancestors along the American continent.